Increasing Student Learning Outcomes, the Material Determines the Length of Time used in Everyday Life Through Demonstration Methods - Agus Aprianto (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Based on the problems that arise in this report, the research objectives that will be achieved through the application of the demonstration method using clock media are to improve mathematics learning outcomes about determining the length of time used in everyday life.in class III This research was conducted at SDN 2 Tegalsumur. This research was conducted through 2 cycles where each cycle consisted of 4 stages, namely planning, implementing, observing / observing, and reflecting. The results of the pre-cycle research with the results: from 18 students only 5 students (29%) obtained complete learning. After the improvement in the first cycle of students who completed learning rose to 14 students (77.78%). improvement of learning cycle II can increase student understanding with the results of achieving completeness to 15 students (83.33%). This increase shows that the methods used in the learning improvement process can improve student learning outcomes.